HOW DOES STUDENTS' ENVIRONMENTAL LITERACY SUPPORT THE SUSTAINABLE DEVELOPMENT GOALS? A LITERATURE REVIEW - Hery Fajeriadi; Fahmi Fahmi; Riza Arisandi (Indonesian Journal of Science Education and Applied Science, 2024)
The importance of environmental literacy as a supporting factor for achieving the Sustainable Development Goals (SDGs), especially SDG 4 (Quality Education). Improving environmental literacy among students is necessary to be able to face global challenges such as climate change and environmental degradation. This study aims to evaluate the extent to which environmental literacy supports quality education related to sustainability issues through a literature review of scientific articles published in national journals. The research method involved a literature search using the keyword “literasi lingkungan” on Google Scholar, with article selection based on inclusion and exclusion criteria. Out of 2280 articles, the 10 most relevant articles were selected for analysis. The results showed that problem-based and experiential learning approaches proved effective in improving students' environmental knowledge and awareness, although cognitive abilities still need to be improved. Improved environmental literacy is also very important in shaping environmentally responsible behavior, which supports the achievement of other SDGs such as SDG 12 (Responsible Consumption and Production), 13 (Climate Action), 14 (Life Below Water), and 15 (Life on Land). The findings of this study emphasize the need for more strategic and effective programs to improve environmental literacy at the education level and its more focused analysis on achieving the SDGs targets.Keywords: Environmental literacy, sustainable development goals, education, attitude. Pentingnya literasi lingkungan sebagai faktor pendukung pencapaian Tujuan Pembangunan Berkelanjutan (SDGs), khususnya SDG 4 (Pendidikan Bermutu). Peningkatan literasi lingkungan pada siswa diperlukan untuk mampu menghadapi tantangan global seperti perubahan iklim dan degradasi lingkungan. Penelitian ini bertujuan untuk mengevaluasi sejauh mana literasi lingkungan mendukung pendidikan bermutu terkait isu keberlanjutan melalui kajian pustaka terhadap artikel ilmiah yang dipublikasikan di jurnal nasional. Metode penelitian yang digunakan adalah pencarian pustaka menggunakan kata kunci “literasi lingkungan” pada Google Scholar, dengan pemilihan artikel berdasarkan kriteria inklusi dan eksklusi. Dari 2280 artikel, dipilih 10 artikel yang paling relevan untuk dianalisis. Hasil penelitian menunjukkan bahwa pendekatan pembelajaran berbasis masalah dan pembelajaran eksperiensial terbukti efektif dalam meningkatkan pengetahuan dan kesadaran lingkungan siswa, meskipun kemampuan kognitif masih perlu ditingkatkan. Peningkatan literasi lingkungan juga sangat penting dalam membentuk perilaku bertanggung jawab terhadap lingkungan, yang mendukung pencapaian SDG lainnya seperti SDG 12 (Konsumsi dan Produksi yang Bertanggung Jawab), 13 (Aksi Iklim), 14 (Kehidupan di Bawah Air), dan 15 (Kehidupan di Daratan). Temuan penelitian ini menekankan perlunya program yang lebih strategis dan efektif untuk meningkatkan literasi lingkungan di tingkat pendidikan dan analisis yang lebih terfokus pada pencapaian target SDGs.Kata kunci: Literasi lingkungan, tujuan pembangunan berkelanjutan, pendidikan, sikap.